2022
DOI: 10.3389/fphar.2022.937413
|View full text |Cite
|
Sign up to set email alerts
|

Glycolysis-Related LINC02432/Hsa-miR-98–5p/HK2 Axis Inhibits Ferroptosis and Predicts Immune Infiltration, Tumor Mutation Burden, and Drug Sensitivity in Pancreatic Adenocarcinoma

Abstract: Pancreatic adenocarcinoma (PAAD) is a malignant cancer with high incidence and mortality. Glycometabolic rearrangements (aerobic glycolysis) is a hallmark of PAAD and contributes to tumorigenesis and progression through numerous mechanisms. This study aimed to identify a novel glycolysis-related lncRNA-miRNA-mRNA ceRNA signature in PAAD and explore its potential molecular function. We first calculated the glycolysis score for each PAAD patient by the ssGSEA algorithm and found that patients with higher hallmar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 95 publications
0
11
0
Order By: Relevance
“…61 Tan et al constructed a novel glycolysis-related LINC02432/hsa-miR-98-5p/HK2 ceRNA network that was markedly associated with ferroptosis, immune infiltration, and drug sensitivity. 62 To our best knowledge, no study has revealed the pathogenesis of lncRNA RP11-138A9.1, RP11-96D1.11, and RP4-773 N10.4 in periodontitis yet. Recent investigations have gradually demonstrated that the novel lncRNA profiles of periodontitis patients are significantly different from that of healthy controls, and some new potential mechanisms and roles of lncRNA in periodontitis have been gradually discovered by microarray and genome-wide sequencing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…61 Tan et al constructed a novel glycolysis-related LINC02432/hsa-miR-98-5p/HK2 ceRNA network that was markedly associated with ferroptosis, immune infiltration, and drug sensitivity. 62 To our best knowledge, no study has revealed the pathogenesis of lncRNA RP11-138A9.1, RP11-96D1.11, and RP4-773 N10.4 in periodontitis yet. Recent investigations have gradually demonstrated that the novel lncRNA profiles of periodontitis patients are significantly different from that of healthy controls, and some new potential mechanisms and roles of lncRNA in periodontitis have been gradually discovered by microarray and genome-wide sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…IL‐10 was identified as a Th2 cytokine that downregulates inflammatory cytokines produced by Th1 61 . Tan et al constructed a novel glycolysis‐related LINC02432/hsa‐miR‐98‐5p/HK2 ceRNA network that was markedly associated with ferroptosis, immune infiltration, and drug sensitivity 62 . To our best knowledge, no study has revealed the pathogenesis of lncRNA RP11‐138A9.1, RP11‐96D1.11, and RP4‐773 N10.4 in periodontitis yet.…”
Section: Discussionmentioning
confidence: 99%
“…Our selective approach contrasts with that of other previously published works on related matters, and we hypothesize that it is of higher clinical translational relevance. Previous studies aimed at developing miRNA-based PC diagnostics are technologically limited, as they did not integrate the real-world datasets [ 25 27 ] or they relied on somewhat outdated computational algorithms [ 28 32 ]. Moreover, others have suggested a circulating three microRNA panel (miR-642b, miR-885-5p, and miR-22) for blood-based detection of PC [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of sirtuins6 in pancreatic cancer (PC) can lead to ferroptosis in cells as well as promote LA production and enhance HK2 and LDHA ( 215 ). Besides, the LINC02432/Hsa-miR-98–5p/HK2 axis associated with glycolysis regulates the ferroptosis pathway in PC ( 216 ). Recombinant pyruvate dehydrogenase kinase isozyme 4 mediated glycolysis in liver fibrosis affects the susceptibility of hepatic stellate cells to ferroptosis ( 217 ).…”
Section: The Regulated Programmed Cell Death and Glycolysismentioning
confidence: 99%